Blott on the landscape - Sharpe, Tom 1928-2013 (Overlook Press, 1999)
A group of locals try to stop a proposed highway.
Keywords: Umweltpolitik; Environmental policy -- Fiction; Gardeners -- Fiction; Humorous fiction.; Legislators -- Fiction; Satire.; Fiktionale Darstellung; Humorous stories; Satire